EXCISE DUTY ON SWEETENED DRINKS - Baturan, Luka; Cvjetković, Cvjetana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
In this paper the authors consider the possibility of introduction excise duty on sweetened drinks in Serbian tax system. The analysis is focused on the study of the basic effects of this fiscal instrument, such as an increase in budget revenues and reduction of the consumption of excise goods. This paper attempts to find the optimal form of excise duty depending on formulated objectives.